2021
DOI: 10.1016/j.celrep.2021.109722
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation is required to maintain both DNA replication timing precision and 3D genome organization integrity

Abstract: DNA methylation is required to maintain both DNA replication timing precision and 3D genome organization integrity Graphical abstract Highlights d DNA hypomethylation is associated with single-cell replication timing heterogeneity d Hypomethylation induces loss of allelic replication at cancerrelated gene loci d Hypomethylation alters higher-order genome architecture of PMD boundaries d Non-canonical H3K4me3-H3K9me3 domains form to protect silent late replication

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 118 publications
1
36
0
Order By: Relevance
“…DNA methylation loss occurs primarily within PMDs, which largely coincide with late replication timing domains 8,9 , are enriched in higher order chromatin compartment B 10 , and tend to be associated with the nuclear lamina 7 . Cancer-associated DNA methylation loss is accompanied by changes in replication timing and 3D genome organization 11 . Replicative senescence alters 3D genome compartmentalization 1214 .…”
mentioning
confidence: 99%
“…DNA methylation loss occurs primarily within PMDs, which largely coincide with late replication timing domains 8,9 , are enriched in higher order chromatin compartment B 10 , and tend to be associated with the nuclear lamina 7 . Cancer-associated DNA methylation loss is accompanied by changes in replication timing and 3D genome organization 11 . Replicative senescence alters 3D genome compartmentalization 1214 .…”
mentioning
confidence: 99%
“…Interestingly, DNA methylation was found to intrinsically modulate chromatin structure and function by increasing chromatin condensation in peri-centromeric regions, decreasing the overall DNA flexibility, and favoring the heterochromatin state [ 122 ]. Further, it has been shown that cancer-related methylation loss is associated with the deregulation of 3D genome organization leading to the disruption of the genome compartmentalization [ 123 ]. DNA methylation can also inactivate TAD boundaries leading to the concomitant activation of key cancer drivers by enhancers located outside their normal TADs through long-range chromatin interactions [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…S4B), suggesting that DNMT3B may exert its catalytic activity at target regions through long-range interactions. Three-dimensional chromatin structure and DNA methylation are implicated in multiple developmental processes [57], but the precise role of DNMT3B in these processes is not fully characterized. Recent observations suggest that in stem and progenitor cells long loops connecting even dozens of mega bases apart may be anchored in large DNA methylation “grand canyons” [58].…”
Section: Discussionmentioning
confidence: 99%